2014
DOI: 10.3390/soc4030363
|View full text |Cite
|
Sign up to set email alerts
|

Intercultural Dating at Predominantly White Universities in the United States: The Maintenance and Crossing of Group Borders

Abstract: Abstract:The increased representation of minority students on the campuses of predominantly White universities in the United States presents increased opportunities for intercultural contact. Studying dating experiences across racial and ethnic lines has been used to determine the existence of a post-racial America. While most previous research has examined general racial/ethnic and gender differences in intercultural college dating experiences, this study analyzes precollege and college-going friendship diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The only exception in the pattern found in this study pertained to responses to LA targets, such that desire for social interaction with LA targets varied as a function of their attractiveness. These results from the Caucasian sample suggesting that positive responses to attractive opposite-sex persons as well as negative reactions toward attractive same-sex persons emerged more strongly for European Caucasians and LAs than for targets from other ethnic backgrounds fit with findings indicating that Caucasians seem to prefer Whites and LAs as potential partners (Feliciano et al, 2009), that mate poachingwhich might enhance the sensitivity to rivalry-is more frequent in Europe and LA than in other (i.e., AS or African) cultures (Schmitt et al, 2004), and that LA students are more likely than other ethnic groups to date interculturally (Keels & Harris, 2014). Moreover, regarding partner preferences, the ''Latino-White boundary'' seems to be less rigid than other ethnic barriers: Latino Americans tend to prefer other Latinos or Caucasians as mates (Feliciano, Lee, & Robnett, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…The only exception in the pattern found in this study pertained to responses to LA targets, such that desire for social interaction with LA targets varied as a function of their attractiveness. These results from the Caucasian sample suggesting that positive responses to attractive opposite-sex persons as well as negative reactions toward attractive same-sex persons emerged more strongly for European Caucasians and LAs than for targets from other ethnic backgrounds fit with findings indicating that Caucasians seem to prefer Whites and LAs as potential partners (Feliciano et al, 2009), that mate poachingwhich might enhance the sensitivity to rivalry-is more frequent in Europe and LA than in other (i.e., AS or African) cultures (Schmitt et al, 2004), and that LA students are more likely than other ethnic groups to date interculturally (Keels & Harris, 2014). Moreover, regarding partner preferences, the ''Latino-White boundary'' seems to be less rigid than other ethnic barriers: Latino Americans tend to prefer other Latinos or Caucasians as mates (Feliciano, Lee, & Robnett, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…While social scientists have examined patterns of marriage and cohabitation in young adulthood, they have paid less attention to “dating” (i.e., romantic involvement outside of a co-residential relationship) in this period (for exceptions see Blackwell and Lichter 2004; Sassler and Joyner 2012; Keels and Harris 2014; McClintock 2010). Studies that focus on population-based samples are a case in point.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown in previous studies that ethnic diversity of friendships influences interethnic dating (Clark-Ibáñez & Felmlee 2004, Keels & Harris 2014, and I argued that a possible source of this effect can be the change of preferences. Results supported the hypothesis that having Roma friends increased the probability that non-Roma respondents find their Roma classmates attractive, and also that they would date with Roma classmates.…”
Section: Discussionmentioning
confidence: 99%
“…Are they additional, or one dominates the other when both effect is entered in the model? Examples from previous research can be found for no effect of group heterogeneity (on the school level) beyond an existing effect of friendship diversity (ClarkIbáñez & Felmlee 2004), and for additional effect of group (college) heterogeneity and friendship diversity (Keels & Harris 2014). As classes are relatively small in contrast to the groups analyzed by these studies, an additional effect beyond friendship diversity may be assumed (H.3.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation